18α‐glycyrrhetinic acid extracted from Glycyrrhiza radix inhibits proliferation and promotes apoptosis of the hepatic stellate cell line. Issue 6 (25th April 2013) - Zong, Lei; Qu, Ying; Xu, Ming Yi; Dong, Yu Wei; Lu, Lun Gen
<x xml:space="preserve">Abstract</x> Objective To evaluate the effect of 18α‐glycyrrhetinic acid (18α‐GA) on the proliferation and apoptosis of hepatic stellate cells (HSCs) and its underlying mechanisms. Methods HSCs (both human and rat HSCs) were pretreated with or without selective peroxisome proliferator‐activated receptor‐γ (PPAR‐γ) antagonist, GW9662, before 18a‐GA treatment. Cell cycle and apoptosis of HSCs were analyzed by flow cytometry, and changes in cell cycle and apoptosis‐related proteins were analyzed by Western blot. The effect of 18α‐GA on nuclear factor kappa‐light‐chain‐enhancer of activated B cells (NF‐κB) DNA‐binding activity was measured by ArrayStar transcription factor activity assay. Results 18α‐GA markedly reduced LX‐2 cell numbers by 14.8% and 31.2% after 48 h and 72 h of treatment, respectively (P < 0.05). 18α‐GA also significantly increased the percentage of LX‐2 cells in phase G0/G1 and decreased it in phase S after treated for 48 h and 72 h compared with the control group. 18α‐GA increased apoptosis to 6.8% at 48 h, compared with control (2.5%), and at 72 h the percentages of apoptotic cells in control and the treatment groups were 3.1% and 15.6%, respectively, in LX‐2 cells (P < 0.01). Similar changes occurred in CCl4‐cirrhotic fat‐storing cells. Furthermore, 18α‐GA induced expression of PPAR‐γ and altered some cell cycle and apoptosis‐related proteins. 18α‐GA also inhibited NF‐κB DNA‐binding activity. All these effects were abolished by GW9662. Conclusions 18α‐GA inhibits the proliferation of activated HSCs and induces apoptosis in culture. It also increases PPAR‐γ expression and decreases NF‐κB DNA‐binding activity, which may be involved in these effects.